Learnings for a toolbox - Sujaya Rathi; Vivek Vaidyanathan (2016)
Institutional capacity and knowledge of faecal sludge management is critical. An assessment – survey questionnaire, conducted by the authors and presented in this paper articulates sanitation systems requirements by different stakeholders namely funders, consultants and city managers, specifically in the aspects of technology, institutions, regulations, finance and monitoring. These learnings have been analyzed and incorporated into the design of a toolbox which is being developed by the Asian Institute of Technology. An engagement with stakeholders, before the design of the toolbox, is a critical requirement to ensure relevance and usability of any toolbox/knowledge product in terms of content, functionality and user experience.